Hand Pollination of Tomato for Breeding and Seed Production - Monica Ozores-Hampton (EDIS)
Hand pollination is a technique that is used for breeding new tomato varieties with desirable characteristics such as plant vigor, disease resistance, and uniform fruit quality and plant growth; since tomatoes have complete flowers and are self-pollinated, it usually is unnecessary to hand pollinate the flowers for fruit production. This 4-page guide illustrates selection and emasculation of flowers from the plant receiving pollen, pollen collection and drying, and pollination of the stigma. Written by Monica Ozores-Hampton, and published by the UF Department of Horticultural Sciences, August 2014. (Photo credit: Monica Ozores-Hampton)